Integrative transcriptomic profiling of mRNA, miRNA, circRNA, and lncRNA in alveolar macrophages isolated from PRRSV-infected porcine - Peng, Ouyang; Xia, Yu; Wei, Ying; Zeng, Siying; Zou, Chuangchao; Hu, Fangyu; Xu, Qiuping; Huang, Yihui; Geng, Rui; Hu, Guangli; Cao, Yongchang; Zhang, Hao (Frontiers in Immunology, 2023)
The porcine reproductive and respiratory syndrome virus (PRRSV) continues to pose a significant threat to the global swine industry, attributed largely to its immunosuppressive properties and the chronic nature of its infection. The absence of effective vaccines and therapeutics amplifies the urgency to deepen our comprehension of PRRSV's intricate pathogenic mechanisms. Previous transcriptomic studies, although informative, are partially constrained by their predominant reliance on in vitro models or lack of long-term infections. Moreover, the role of circular RNAs (circRNAs) during PRRSV invasion is yet to be elucidated. In this study, we employedadopted an in vivo approach, exposingsubjecting piglets to a PRRSV challenge over varied durations of 3, 7, or 21 days. Subsequently, porcine alveolar macrophages were isolated for a comprehensive transcriptomic investigation, examining the expression patterns of mRNAs, miRNAs, circRNAs, and long noncoding RNAs (lncRNAs). Differentially expressed RNAs from all four categories were identified, underscoring the dynamic interplay among these RNA species during PRRSV infection. Functional Eenrichment analyses indicatesuggest that these differentially expressed RNAs, as well asor their target genes, play a pivotal role in immune related pathways. For the first time, we have integrated circRNAs into the lncRNA-miRNA-mRNA relationship, constructing a competitive endogenous RNA (ceRNA) network. Our findings highlight the immune-related genes, CTLA4 and SAMHD1, as well as their associated miRNAs, lncRNAs, and circRNAs, suggesting potential therapeutic targets for PRRS. Importantly, we corroborated the expression patterns of selected RNAs through RT-qPCR, ensuring consistency with our transcriptomic sequencing data. This study sheds lights onoffers a valuable insight into the intricate RNA interplay during PRRSV infection and provides a solid foundation for future therapeutic strategizing.